Inferior Dislocation of Shoulder Complicated with Undisplaced Greater Tuberosity Fracture, Rupture of the Supraspinatus Tendon, and Brachial Plexus Injury in the Elderly: Case Report and Literature Review - Angelo V. Vasiliadis; Christos Kalitsis; Theofanis Kantas; George Biniaris (Case Reports in Orthopedics)
Inferior dislocation of the shoulder, also called luxatio erecta, is a rare form of the otherwise common shoulder dislocation. It appears in less than 0.5% of all shoulder dislocations. An awareness of associated potential axillary artery injury, brachial plexus complications, and rotator cuff tears is important in this rare entity and should be excluded with a high index of suspicion. In our case report, we have an 83-year-old female who inferiorly dislocated her dominant shoulder with brachial plexus injury and musculotendinous injury, which was caused by an accidental fall. The dislocation was manually reduced at the emergency department. After 18 months of conservative treatment with physical therapy, the range of motion and muscle strength of the shoulder recovered to a satisfactory mobile level according to the patient’s demands.